TENG-Boosted Smart Sports with Energy Autonomy and Digital Intelligence - Wang, Yunlu; Gao, Zihao; Wu, Wei; Xiong, Yao; Luo, Jianjun; Sun, Qijun; Mao, Yupeng; Wang, Zhong Lin (Nano-micro letters, 2025)
Highlights The recent advancements in triboelectric nanogenerator (TENG)-based sports equipment for smart sports are comprehensively reviewed. Thorough explorations of combining TENG technology and artificial intelligence/machine learning techniques to enhance smart sports are examined in this study. Comprehensive discussions on the opportunities and challenges of TENG-based smart sports are summarized. Technological advancements have profoundly transformed the sports domain, ushering it into the digital era. Services leveraging big data in intelligent sports—encompassing performance analytics, training statistical evaluations and metrics—have become indispensable. These tools are vital in aiding athletes with their daily training regimens and in devising sophisticated competition strategies, proving crucial in the pursuit of victory. Despite their potential, wearable electronic devices used for motion monitoring are subject to several limitations, including prohibitive cost, extensive energy usage, incompatibility with individual spatial structures, and flawed data analysis methodologies. Triboelectric nanogenerators (TENGs) have become instrumental in the development of self-powered devices/systems owing to their remarkable capacity to harnessing ambient high-entropy energy from the environment. This paper provides a thorough review of the advancements and emerging trends in TENG-based intelligent sports, focusing on physiological data monitoring, sports training performance, event refereeing assistance, and sports injury prevention and rehabilitation. Excluding the potential influence of sports psychological factors, this review provides a detailed discourse on present challenges and prospects for boosting smart sports with energy autonomy and digital intelligence. This study presents innovative insights and motivations for propelling the evolution of intelligent sports toward a more sustainable and efficient future for humanity.